Fabrication and resonant behavior of PZT thick film cantilever for BioChip - Kim, HJ; Kim, YB; Kang, JY; Kim, TS (TAYLOR & FRANCIS LTD, 2002)
PZT(52/48) thick films with an Pb-based complex oxide (PCW) additive were prepared on Pt/TiO2/YSZ/SiO2/Si substrate by new hybrid method based on the screen printing. It is found that solinfiltration for thick films fabrication process significantly improves the electrical properties due to the improved structural compactness. By applying these high quality piezoelectric thick films on micro cantilever devices, a highly sensitive thick film cantilever for mass(ng-square) detection devices is successfully fabricated. Resonant frequency and displacement of PZT-0.12PCW thick film cantilever for biochip are measured by laser vibrometer system as a function of cantilever size (width, length). We change the added mass from 4ng to 5square through Au deposition. The shorter cantilever is more sensitive for mass change and it is found that the sensitivity of cantilever decreases due to viscous damping effect in liquid. Finally, the application of these PZT-0.12PCW thick film cantilever devices to a protein detector is discussed.
Keywords: SILICON